2022
DOI: 10.3389/fevo.2022.894344
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Senescence in Two Lemur Lineages

Abstract: The relationship between age and reproductive performance is highly variable across species. Humans and some cetaceans exhibit an extreme form of reproductive senescence in that female reproduction ceases years or even decades before average life expectancy is reached. However, neither the existence of reproductive senescence in some taxa nor its absence in others is fully understood. Comparative data from other long-lived mammals may contribute to a more comprehensive understanding of the evolution of menopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Besides these, other factors could be predicted to influence SF ageing. For instance, evidence for reproductive ageing has been shown to be stronger in laboratory and captive animals compared to wild ones (Nussey et al, 2013;Zajitschek et al, 2020;Kappeler et al, 2022). Additionally, domestic animals, which were used in a majority of studies found in our systematic review, are kept in semi-controlled conditions and are killed off prior to reaching a senescent age (i.e., post their "prime").…”
Section: Factors That Could Influence Seminal Fluid Ageing Ratesmentioning
confidence: 99%
“…Besides these, other factors could be predicted to influence SF ageing. For instance, evidence for reproductive ageing has been shown to be stronger in laboratory and captive animals compared to wild ones (Nussey et al, 2013;Zajitschek et al, 2020;Kappeler et al, 2022). Additionally, domestic animals, which were used in a majority of studies found in our systematic review, are kept in semi-controlled conditions and are killed off prior to reaching a senescent age (i.e., post their "prime").…”
Section: Factors That Could Influence Seminal Fluid Ageing Ratesmentioning
confidence: 99%
“…On the other hand, quadratic age could indicate reproductive senescence, suggesting a “prime” reproductive age around which infant survival may decrease due to factors like lack of dam experience (before prime age) or a decline in milk quality and quantity (after prime age; Tidière et al, 2018); this may suggest differing management strategies to promote infant survival around that prime age. Kappeler et al (2022) found evidence for reproductive senescence in wild red‐fronted lemurs ( Eulemur rufifrons ) and zoo‐housed red lemurs, and Tidière et al (2018) further demonstrated that infant survival of red‐ruffed and black‐and‐white ruffed lemurs initially increased with dam age, then began to decrease as the dam approached reproductive senescence. In some primate taxa, increased dam age was positively associated with infant mortality (de Visser et al, 2022) or the likelihood of stillbirths (Saiyed et al, 2018), while others showed reduced infant survival for both the youngest and oldest dams (Campos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%